Pengaruh Motivasi Dan Semangat Kerja Terhadap Kinerja Karyawan Pada Cipta Karya Aceh - Zahara Zahara; Kamaruddin Kamaruddin; Zulfikar Zulfikar (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This study aims to determine the effect of motivation and employee morale on Acehnese creations. The sample used in this study was 30 Cipta Karya aceh employees. The method in this research is a quantitative method. The results showed that it is known that the t_1 count is 2.889 with a ttable of 1.661, then t table <t count. With a significance level of 0.005 <0.05, this proves that the first hypothesis is accepted, namely that there is an effect of motivation on performance. While the t_3 count above can be seen that t_3 is 2.116 with a ttable of 1.661, then t table < t count. With a significance level of 0.037 <0.05, this proves that the second hypothesis is accepted, namely that there is an effect of morale on performance.